Zika in Pernambuco: rewriting the first outbreak - Carlos Alexandre Antunes de Brito; Cecilia Coelho Moraes de Brito; Augusto César Oliveira; Marilia Rocha; Caio Atanásio; Carolina Asfora; Júlio Dourado Matos; Anton Saraiva Lima; Maria Fátima Militão Albuquerque (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: A Zika virus epidemic was registered in 2015 in Northeast Brazil. In the State of Pernambuco, thousands of classical cases transpired, and in the following months, neurological disturbances in adults and microcephaly in newborns emerged as complications. After the peak of the epidemic, the official system reported only four cases of Zika virus but over 100,000 cases of dengue virus. The vigilance system was unable to retrospectively estimate cases or to issue an alert to officially notified cases with possible inconsistence concerning specific arbovirosis diagnoses. METHODS: To evaluate the frequency of different arbovirosis diagnoses based on clinical-epidemiologic criteria, from January to April 2015, we conducted a hospital-based cross-sectional study retrospectively analyzing suspected cases of arbovirosis. RESULTS: Of 1 , 046 total suspected cases of arbovirus, 895 (86%) were classified as probable Zika virus cases, and 151 (14%) as probable dengue virus cases. The most frequent manifestations in probable Zika virus cases were exanthema (100%), pruritus (50.7%), fever (20.4%) and arthralgia (27.7%). CONCLUSIONS: In contrast to the official data, during the peak months of the arbovirosis epidemic of 2015, most cases were compatible with Zika virus infections. Hospital-based studies, although retrospective and based on secondary data from clinical files, might provide a better estimate of the number of cases relative to currently available data, if derived from several urgent care units of representative areas of a city or state.This would partially retrospectively correct some inconsistences regarding official notifications.